Evaluation of waiting time and associated factors influencing patient satisfaction levels in an outpatient department: A case study of government hospital in Sierra Leone - Jalloh, Abdulai Alpha; Nwosu, Laurine Chikodiri; Baysan, Semra (Science, Engineering and Health Studies, 2023)
The issue of waiting time has received little attention in the delivery of healthcare services in Sierra Leone. The time spent waiting in the hospital has been considered a major indicator in measuring healthcare quality and patient satisfaction with services. However, long waiting time have constituted a substantial impediment to maximizing healthcare quality. This quantitative study employed data collected from 347 patients in an outpatient department using an online survey. The data collected was analyzed using SPSS version 20. Correlation and regression analyzes were conducted to test the relationship and impact among the variables. The findings revealed an overall dissatisfaction with the waiting time to see a doctor, the behavior and professional competency of medical staff, and the service delivery. Furthermore, significant values were obtained for the correlation and effect between the constructs (p<0.05). Therefore, it is recommended that training on effective communication skills should be provided to address perceptions of ill behaviors from hospital staff and aid better working relationships among caregivers, patients and families. The government and hospital administrators should also introduce an online appointment booking system to minimize waiting time.